Metastatic Breast Cancer Coexisting With HER-2 Amplification and EGFR Exon 19 Deletion Benefits From EGFR-TKI Therapy: A Case Report - Jing, Wei; Ma, Jie-Tao; Han, Cheng-Bo (Frontiers in Oncology, 2020)
Background: Patients with different molecular subtypes of breast cancers have different recurrence risks and prognoses. Clinical support and evidence to guide management are absent for patients with breast cancer coexisting with HER-2 amplification and EGFR mutations. Case presentation: We report a case of breast cancer coexisting with HER-2 amplification and EGFR exon 19 deletion (E19 del). The patient presented with solitary pulmonary nodule and enlargement of hilar and mediastinal lymph nodes 2 years after radical mastectomy. Biopsy of the subcarinal lymph node showed suspected adenocarcinoma. The specimen was too small for further immunohistochemistry, but an EGFR E19 del was discovered. Due to the primary diagnosis of EGFR-mutant lung adenocarcinoma, EGFR-TKI gefitinib was administered and resulted in 1 year of stable disease until the patient developed progression in the right pulmonary nodule with new metastatic cervical lymph nodes. According to histopathological findings of re-biopsy of the pulmonary nodule and left cervical and subcarinal lymph nodes, the patient was diagnosed with breast cancer with lung metastasis and multiple lymph node metastases. The patient received multiple anti-HER-2-targeted therapies (trastuzumab for 9.7 months, lapatinib for 9 months, and pyrotinib for 4+ months) and survived for more than 36 months after lung metastasis. Conclusions: This case suggested that breast cancer coexisting with HER-2 amplification and EGFR E19 del may be driven by both HER-2 and EGFR signaling pathways, and patients can benefit from EGFR-TKI and anti-HER-2 therapy.